Effects of brown alga, Stoechospermum marginatum extract on growth performance, body chemical compositions and some serum biochemical parameters in grey mullet, Mugil cephalus (Linnaeus 1758) - Nazanin Kiani; Paria Akbary (تغذیه آبزیان)
Introduction: Distribution of macroscopic algae is high on the shores of the Persian Gulf and the Sea of Oman. On the other hand, sustainable and successful aquaculture depends on maintaining the health of the aquatic species and improving the breeding conditions to achieve the maximum growth in aquatic species and also reduce the costs of the production process. Researchers are looking for new and better approaches to achieve the goal of aquaculture. Using seaweed in aquaculture is expanding due to the presence of nutrients such as antioxidants, essential fatty acids (omega 3 and 6), essential amino acids, vitamins, minerals, carbohydrates and beta-carotene. Using algae in the diet of aquatic animals not only reduces the cost of feeding, but also leads to improve the efficiency of aquatic nutrition, digestion, and strengthening the immune system of fish, and by improving the efficiency of digestion, it also affects the quality of water. Given the importance of grey mullet, Mugil cephalus as one of the commercially important fish species and its ability to grow in earthen ponds as well as adapting to a wide range of temperature, salinity and nutritional conditions, in this research, the effect of brown algae, Stoechospermum marginatum extract on growth performance and some biochemical parameters in the grey mullet blood serum were studied for 60 days. Materials and methods: The experiment was conducted in a completely randomized design with 120  grey mullet (with average weight of 9.56 ± 1.02 g) in 4 treatments and 3 replicates (n = 10 in each replicate) including: control group (T1) without using algae extract, 5 (T2), 10 (T3) and 15 g (T4)  brown algae per kg of diet. In order to measure the growth performance, at the end of the experiment, weight and length of fish were recorded. Chemical analysis of the carcass composition was carried out according to the AOAC standard method. Also, in order to determine the biochemical parameters, blood was taken from the heart using a syringe, and poured into a 2 mL- micro tube. Then, it was centrifuged at 3000 rpm for 10 min and serum was separated and stored at -70°C. Analysis of the data obtained from the measurement of growth indices, carcass composition and some biochemical parameters of blood serum in grey mullet were performed using One-way analysis of variance (ANOVA) and Duncan's multiple range comparison tests. Results: The results showed that at the end of experiment, the highest final weigh (32.89 ± 2.74 g), the highest weight gain (292.56 ± 35.01%) the lowest food conversion ratio (0.95 ± 0.05), the highest voluntary feed intake (1.74 ± 0.42%), the highest crude protein (20.50 ± 1.29%), lowest crude lipid (6.73 ± 1.13%), the highest globulin (4.27 ± 0.12 g/dL), albumin (2.63 ± 0.18 g/dL) and total protein (6.84 ± 0.54 g/dL) were observed in T4. In all of these parameters, T4 showed a significant difference compared to control treatment (p<0.05). The lowest cholesterol and triglyceride were observed in T3 and T4 exhibiting a significant difference compared to the control (T1; p<0.05). Conclusion: The present results suggest that diet containing 15 g/kg Stoechospermum marginatum extract could enhance growth, carcass quality and serum biochemical parameters in Mugil cephalus.